The Concept of Fathering in Child Care During the Covid-19 Pandemic - Mulyana, Indra; Zuhri, Saifuddin; Dimas Aditya, Viedy; Arianto, Toni (STAI Publisistik Thawalib Jakarta, 2023)
Children are a trust that require father-mother parenting aligned with the times, to prevent the impacts of fatherlessness and shape the character of today’s generation. This study explores the implementation of the fathering concept in child-rearing during the pandemic. It employs a qualitative method using a literature study approach. The research sources include the Qur'an (tafsir), books, and school documents. Findings: The phenomenon of fatherlessness has negative effects on children, such as the loss of security, increased school absenteeism, cognitive decline, a higher risk of depression, antisocial behavior, and both physical and psychological distress. To address this, the father's role must be strengthened by implementing positive fatherly values, especially during the Covid-19 pandemic. These values include being a role model, applying consistent parenting habits, giving loving advice, creating a supportive environment, showing wisdom, and always praying for the child's well-being and development. Conclusion: The father's active role is essential in child-rearing to prevent the negative impact of fatherlessness, particularly during the pandemic